Seroprevalence and risk factors of infectious bovine rhinotracheitis in cattle in Gharbia governorate, Egypt: A comparative study of traditional and commercial production systems - Mostafa El-Sayed El-Sheikh; Lotfy Bakar; Mamdouh Fahmy El-Mekawy; Mohammed Ibrahim Eisa; Nasser Zeidan Abouzeid; Mervat Ibrahim Abdelmonim; Sarah Gamal Yousef (Open Veterinary Journal)
Background: Infectious bovine rhinotracheitis (IBR) is a global contagious respiratory disease of ruminants caused by Bovine Herpes virus-1(BoHV-1). It causes substantial financial losses in the dairy industry worldwide and is considered one of the most important causative agents of abortion and reproductive problems in dairy cattle.